PRODUK OLAHAN PEPAYA PADA KWT AL-MUHAJIRIN DI KELURAHAN TAMALAREA JAYA KECAMATAN TAMALANREA - Sitti Arwati; Asriyanti Syarif (JURNAL PENGABDIAN AL-IKHLAS UNIVERSITAS ISLAM KALIMANTAN MUHAMMAD ARSYAD AL BANJARY, 2018)
Community service is to provide an overview of the benefits of papaya fruit and the composition of papaya as a fruit that can also be processed into jam and cake products through counseling. Provide training to housewives regarding the procedure for making jams and cakes from processed papaya. This community service was carried out in Tamalanrea Jaya Village, Tamalanrea District. This community service involves KWT Al Muhajirin  in Tamalanrea Jaya Village as partners. The type of mature papaya that is chosen to be managed because this papaya is easily damaged and decomposes. This community service shows that the counseling and training process provided to partners regarding the importance of consuming papaya, papaya's nutritional content, degenerative diseases caused by lack of fruit consumption and training of cooked papaya products into jams and cakes goes well as seen from the positive response. given by partners and the high participation of partners in counseling and training activities carried out, activeness asks partners because of the desire to obtain information and multiply knowledge, the desire of partners to make processed papaya as a product that can increase family income.Keywords: Diversification, papaya, KWT